A comparison of ground geoelectric activity between three regions of different level of seismicity - A. Ramírez-Rojas; E. L. Flores-Márquez; L. Guzmán-Vargas; J. Márquez-Cruz; C. G. Pavía-Miller; F. Angulo-Brown (Natural Hazards and Earth System Sciences, 2007)
In this work, we present a statistical study of geoelectric time series from three Mexican regions with recognized different levels of seismicity. This study is made by means of both the Higuchi's method and the detrended fluctuation analysis for the detection of fractal behavior. With these methods we present scatter plots corresponding to scaling exponents for short and large lags arisen from crossover points in the geoelectric data. Through these scatter plots we observe a reasonable segregation of clouds of points corresponding to the three mentioned regions. These results permit to suggest that a different level of characteristic seismicity in one region is translated into a different level of geoelectric activity.